Virtual Reality Sebagai Media Pembelajaran Teknik Kendaraan Ringan Otomotif Dalam Era Pendidikan Digital - Fita Lestari, Riska; Lutfi Irawan Rahmat; Ratna Mustika Yasi; Adi Mulyadi; Muhammad Zainal Roisul Amin; Agung Nugroho (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
During the aftermath of the Covid-19 pandemic, educational establishments encounter difficulties in providing comprehensive learning experiences due to the unpredictable circumstances caused by the pandemic. Hence, it becomes crucial for these institutions to prioritize the adoption of digitalized education that allows for accessibility at any time and from any location. However, the field of light vehicle engineering faces its own set of challenges when it comes to delivering intricate materials, primarily due to the size and intricacy of the learning resources. To tackle this issue, a novel approach has been introduced in the form of Virtual Reality (VR)-based learning methods, which prove to be invaluable tools in enhancing comprehension of the subject matter.